Contextual synthesis of IFRS S1: general requirements for financial information to disclose about sustainability - Flórez Ríos, Alejandra Maryed (2024)
The internation standard of financial reporting with information to disclose about sustainability IFRS S1 was issued in June 2023 and entered into force in January 2024. This document’s objective is to present an exploratory synthesis of the main elements stated in the standard. Said identification of central aspects of the standard are secondarily oriented to evidence that the IFRS S1 centers its concerns in protecting the financial interests of capital providers, with no concern whatsoever for protecting nature or defending optimal ecosystem conditions for life. The standard is an appendix of the internation financial framework. The objective of the IFRS S1 standard is to reveal information about risksand opportunities related to sustainability that are useful for investors, lenders or other existing creditors and potentials to make decisions related to providing resources to the entity. Understanding nature and outreach of the regulations object of study contributes to understand it as an extension of the financial paradigm of organization reports, which far from being a disruptive model, emergent or alternative, is constituting to the insight of this tools at the service of the international financial capital. This paper is made by a qualitative, deductive, documental, exploratory, conceptual and non-experimental study. An initial subtitle of historical and conceptual context is presented about the terminology “sostenibilidad” and “sustentabilidad”, as a necessary guide for the reader to form their own judgment about the moral foundation of the standard.